5th EAA International Symposium on Hydroacoustics - Archives of Acoustics, Editorial Board (Archives of Acoustics, 2005)
The 5th EAA International Symposium on Hydroacoustics together with domestic XXII Symposium on Hydroacoustics took place in Puck at the Sport and Training Centre DELFIN, May 16–19, 2005. The 5th EAA International Symposium on Hydroacoustics was organized by Naval Academy in Gdynia, Gda´nsk University of Technology, European Acoustic Association, Polish Acoustical Society (Gda´nsk Division) and Ultrasonic Division of the Committee on Acoustics of the Polish Academy of Sciences. Prof. Gra˙zyna Grelowska, the vice-rector of Naval Academy in Gdynia, was the chairman of the Organizing Committee. There were professors from famous European universities in the Scientific Committee. The professors arrived from, among others, Germany, Denmark, Russia, France, Italy, Greece, Turkey and Poland. The chairman of Scientific Committee was Prof. Eugeniusz Kozaczka who is the president of Polish Acoustical Society and who represents Poland in European Acoustics Association. The main aim of the symposium is giving opportunity to exchanging experiences and information among research centres dealing with underwater acoustics and ultrasound. The Symposium subject included: • sound propagation in the sea, • ambient and ship noise, • nonlinear acoustics, • ultrasonic transducers, • signal and data processing, • sonar systems, • other topics related to underwater acoustics. 70 scientists have registered to the Symposium representing research centres mainly from Poland but also from other European countries and Canada. 30 papers were presented, including 3 following invited papers: • E. Kozaczka – Modern applications of maritime technology. • A. Bobrowicz – Obrona bierna okr˛etów Marynarki wojennej RP. • I. Didenkulov, S. Muyakshin, D. Selivanovsky – Rotation of small particles in sound field and possible mechanism of sound perception. All accepted papers were published in the periodical “Hydroacoustics” vol. 8.